Estimating and forecasting the impact of inflation on economic growth in Nigeria using threshold analysis - David O. K. Okoroafor; Sesan O. Adeniji; Timilehin Olasehinde (CBN Journal of Applied Statistics, 2018)
This study examined the causal relationship between inflation and economic growth as well as estimating threshold and forecasting of inflation in Nigeria for the period of 1961 2016. The study employed Granger causality test, Au- toregressive Distributed Lag (ARDL), Autoregressive Integrated Moving Av- erage (ARIMA) and a multivariate time series Vector Autoregressive (VAR) models. Granger causality test result showed that inflation does not granger cause economic growth and neither does economic growth granger cause inflation during the period of study. Using broad money supply to GDP as control variable, an inflation threshold of 14% -15% both in the short run and long run was established for Nigeria. As for the forecasting of inflation, the findings showed that VAR (1) could forecast inflation rate in Nigeria with high degree of accuracy. Hence, this result is vital for monetary policy formula- tion and need to be taken into consideration as a complement to the approach currently employed by the Central Bank of Nigeria in the targeting of a single digit inflation rate.
Keywords: E31; C53; E52; O40; 330; ARDL; ARIMA; Economic Growth; Forecasting; Inflation Threshold VAR